Harmonisasi Alam dan Budaya: Mewujudkan Keberlanjutan Wisata Melalui Peranan Ekonomi Masyarakat Kiyu Desa Hinas Kiri Kabupaten Hulu Sungai Tengah - Rahma SAS, Cindi Novita; Damaiyanti, Varinia Pura; Pratama, Muhammad Daffa'; Khotimah , Usnul; Rifani, Muhammad; Rasidah, Miftah; Rahmadini, Nasifa Noor; Hawa, Siti; Koso, Difa Salsabila; Huda, Nurul; Pratama, Muhammad Bagus (Prodi Sosiologi FISIP ULM, 2025)
The shift in tourist preferences toward experience-based tourism and environmental responsibility presents significant opportunities for developing Hinas Kiri Village as a tourist destination. Natural attractions such as the hiking trails of Mount Halau-Halau and the cultural richness of the Dayak Meratus people are the main draws that can be further optimized. The development of this village follows a community empowerment approach through the “live-in” method, where the team resides with the local community to build deeper connections and understand their lifestyle and wisdom. One of the key steps is holding Village Discussions, which explore the community's creative economic potential. The focus is on handicrafts and simpai accessories, which hold high cultural value and can become the village's signature products. These products are expected not only to increase community income but also to introduce Dayak Meratus culture to visiting tourists. Community empowerment is carried out through various trainings, including craft skills, business management, and marketing. Additionally, collaboration with the government and tourism-aware groups (POKDARWIS) is crucial for creating a sustainable tourism ecosystem. Infrastructure support, such as road access, tourism facilities, and appropriate promotion, is needed to make the village's tourism potential more widely known and attract tourists. However, this development must be carried out wisely, balancing economic growth, cultural preservation, and environmental sustainability. The natural environment and customs of the Dayak Meratus people are important identities that must be preserved and are expected to develop sustainably, providing economic benefits for the local community while preserving cultural heritage and maintaining the natural environment, which is the village's primary asset.